Decentralization of public healthcare services in the Province of Sumatera Utara, Indonesia - Februati Trimurni; Norma Mansor (Intelektual Pustaka Media Utama, 2020)
The research examined the effectiveness of decentralization program on the healthcare sector at the provincial level in the context of political and administrative decentralization. It adopted qualitative approach and employed the technique of in-depth interview, observation on documentation. Informants consist of public servants, practitioners, community and relevant stakeholders. The implementation of decentralization does not work that ideal for some reason: the devolution and the decentralization programs are not conducted simultaneously, mutually support and complimentary; the lack of local apparatus capabilities to understand and carry out the principles and the practices of the programs in the field; the limitation of financial sources and support to conduct the programs.